Analysis of the Gyeonggi Bay Ecomuseum as a Wide-Area Ecomuseum - Lee, Hanju (Advances in Social Sciences Research Journal, 2021)
This study aims to examine the features of the creation and operation of ecomuseums at wide-area and (metropolitan) local government levels and to analyze their improvements and limitations based on an analysis of a case study on the “Gyeonggi Bay Ecomuseum.” This study also reveals the necessity and direction for ecomuseums led by metropolitan local governments. It attempts to find ways to expand the Gyeonggi Bay Ecomuseum and apply lessons from this ecomuseum to other planned wide-area ecomuseums in South Korea. Overall, this study intends to derive the sustainability of wide-area ecomuseums, and their utility and potential as a means to revitalize the region. The Gyeonggi Bay Ecomuseum is a meaningful case study as it was created in a wide area called the Gyeonggi Bay and was led by a metropolitan local government, along with the official claim as an ecomuseum; the museum creation project also progressed in a phased approach. However, there are issues such as organization problems of the ecomuseum and the absence of resident participation, integrated programs, and an archive center. Therefore, this study presents measures to overcome these obstacles: the establishment of a core ecomuseum and an exhibition center, the development of joint programs, the continuous security of funds and human resources, and measures to generate economic benefits for residents. This study also suggests spatial/functional expansion from being the “Gyeonggi Bay Ecomuseum” to the “Gyeonggi Province Ecomuseum.” Keywords: Ecomuseum, Wide-area unit, Lead of local governments, Gyeonggi Bay, Regional revitalization